MICROFINANCE AND ENTERPRISES – CASE OF ALBANIA - Loca, Semiha; Kola, Forcim (European Scientific Journal, ESJ, 2013)
Small and micro entrepreneurs are often considered as a risky client group for banks, because they lack collateral or the capacity to convince banks that they are able to get and repay a business loan. The costs of processing small loans and the risks involved in lending to micro businesses make financial institutions hesitant to develop services for small and micro entrepreneurs. Few entrepreneurs have or can rise from family and friends, but even established businesses often need to raise more finance than can be provided by retained earnings. This paper aims to bring evidences to analyze how and to what the microfinance services in Albania has affected the entrepreneurial activity and how these entrepreneurial companies can benefit by using it. In order to do so, we focus on different aspects of microfinance impact to firms credited by MFIs in Albania. The methodology combined the application of both quantitative and qualitative tools including questionnaire on different indicators addressed to beneficiaries. Qualitative information was collected through Focus Group Interviews and Semi-structured interviews to understand the situations that people face how they use and perceive microfinance, especially enterprises served by microfinance sector in Albania. The paper will be organized in the way of bringing facts and figures about how the microfinance Institutions (MFIs) in Albania are supporting the small and medium enterprises with their services, considering the perspective of increasing the number of new small entrepreneurship practices as supposed to be supported by microfinance institutions in Albania.